1986
DOI: 10.1111/j.1751-1097.1986.tb05528.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Generation of Hydroxyl Radicals by Hematoporphyrin Derivative and Light

Abstract: In a reaction mixture containing hematoporphyrin derivative, deoxyribose, Fe3+‐EDTA and either methionine or tryptophan, hydroxyl radicals were formed during illumination with visible light. When either hematoporphyrin derivative, Fe3+‐EDTA or the amino acid was omitted from the reaction mixture, the generation of hydroxyl radicals ceased. These observations suggest an iron‐catalyzed Haber‐Weiss reaction, involving superoxide and hydrogen peroxide in the generation of hydroxyl radicals. It could be shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The defect in ferrochelatase results in accumulation of protoporphyrin (Bottomley et al, 1975;Cox, 1997;Lim and Cohen, 1999), which may be produced in immature red blood cells, released into the plasma, and accumulate in the cell membranes of endothelial cells due to its hydrophobicity (Brun and Sandberg, 1991). Numerous in vitro studies have shown the generation of reactive oxygen species (ROS), such as singlet oxygen ( 1 O 2 ), hydroxyl radicals ( OH), and superoxide anion radicals (O 2 À ), during photodynamic reactions with various porphyrins (Buettner and Oberley, 1980;Torinuki and Miura, 1983;Blum and Grossweiner, 1985;Van Steveninck et al, 1986;Carraro and Pathak, 1988;Haseloff et al, 1989;Herrmann et al, 1996). Various cytotoxic effects of these ROS have been shown with endothelial cells in vitro (Sacks et al, 1978;Kvietys et al, 1989;Knepler et al, 2001;Kwon et al, 2001).…”
mentioning
confidence: 98%
“…The defect in ferrochelatase results in accumulation of protoporphyrin (Bottomley et al, 1975;Cox, 1997;Lim and Cohen, 1999), which may be produced in immature red blood cells, released into the plasma, and accumulate in the cell membranes of endothelial cells due to its hydrophobicity (Brun and Sandberg, 1991). Numerous in vitro studies have shown the generation of reactive oxygen species (ROS), such as singlet oxygen ( 1 O 2 ), hydroxyl radicals ( OH), and superoxide anion radicals (O 2 À ), during photodynamic reactions with various porphyrins (Buettner and Oberley, 1980;Torinuki and Miura, 1983;Blum and Grossweiner, 1985;Van Steveninck et al, 1986;Carraro and Pathak, 1988;Haseloff et al, 1989;Herrmann et al, 1996). Various cytotoxic effects of these ROS have been shown with endothelial cells in vitro (Sacks et al, 1978;Kvietys et al, 1989;Knepler et al, 2001;Kwon et al, 2001).…”
mentioning
confidence: 98%
“…Light activation of the localized porphyrin induces damage to mitochondria, cellular organelles, membranes, DNA, and specific proteins by singlet oxygen, produced under aerobic conditions and possibly by hydroxyl radicals (Reviewed by Moan, 1986;& Van Steveninck et al, 1986). Photodynamic therapy is based on administration of an HPD solution to the cancer patient and later on, illumination of the tumour by a 630nm laser light beam.…”
mentioning
confidence: 99%
“…Increasing evidence indicates that cytotoxicity induced by PDT is mediated through the photochemical generation of singlet oxygen via a Type II reaction (Spikes). In addition, a number of studies have documented that various other reactive species -including hydroxyl radicals, hydrogen peroxide and superoxide anion -can be produced by porphyrin photosensitization (12). The main purpose of the present study was to test the effectiveness of liposomal delivered protoporphyrindisodiumsalt for photodynamic therapy.…”
Section: Discussionmentioning
confidence: 98%